Evaluasi Pengalaman Pengguna pada Media Perkuliahan Daring di Masa Pandemi COVID-19 Menggunakan UX Curve (Studi Kasus Mahasiswa Jurusan Teknologi Informasi Politeknik Negeri Malang) - Bhaktiar Adi Nugraha; Diah Priharsari; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The COVID-19 pandemic that has occurred since the beginning of 2020 has had a major impact on various aspects, one of which is in the education sector. Teaching and learning activities that are usually carried out face-to-face in class are currently carried out using distance learning methods. The Department of Information Technology, State Polytechnic of Malang, as a part of the higher education institution, has also carried out a transformation through the implementation of online lectures using online learning media, namely LMS Polinema. The use of LMS Polinema gets various responses from users. This research then aims to document how long-term user experience is and how the acceptance and use of online learning media during the COVID-19 pandemic using the UX Curve method combined with the viewpoints of the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Respondents who became the object of research were 10 students of the Department of Information Technology, State Polytechnic of Malang, aged 19-22 years. There were 4 aspects evaluated, namely Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. The results of the analysis show that the average curve on the Performance Expectancy aspect has the most significant improving. In addition, the Performance Expectancy aspect is the aspect that most influences the user experience which has the highest number of respondents' comments for 80 reasons, consisting of 43 positive reasons and 37 negative reasons.